The Effect of Question Answer Relationships (QARs) Strategy of Students’ Reading Comprehesion - Darma, Suci Dwina (Jurnal Pendidikan Vokasi Raflesia, 2024)
This research aimed to know the impress of Question Answer Relationships (QARs) Strategy on students’ reading comprehension. The subjects of this research were the first semester students of STKES Al Fatah Bengkulu in 2024/2025 academic years which consists 62 students. This research used experimental research was divided into two classes. They are experimental class and control class. The data was obtained by using reading comprehension tests in students’ skills of understanding reading text of report texts in order to complete data. The data analysis was applied t – test analysis. The research result showed the Question Answer Relationships (QARs) Strategy gave significant effect toward sudents’ reading comprehension.